POLA KOMUNIKASI ANTARPRIBADI PELATIH DAN SISWA DALAM MEMBANGUN MOTIF BEROLAHRAGA SEPAK BOLA USIA DINI - R. Rama Adhypoetra; Citra Eka Putri (Jurnal Pustaka Komunikasi, 2019)
The purpose of this study was to find out the Interpersonal Communication Patterns of SSB ASTAM early-age Football Coaches and to know what the Obstacle Factors and supporters were getting early SSB ASTAM Football Coaches in doing Interpersonal Communication Activities. This study uses the Competency Theory according to Spencer Spencer. A qualitative approach to the constructivism paradigm. a firm coach on the rules imposed by the SSB ASTAM academy with parents of students, the trainer builds good communication with parents of students. The self-concept that the coach has. Interpersonal Communication Patterns carried out by early SSB ASTAM Trainers can work effectively because of the factors that support the trainer to communicate. The problems that come to their students and to the team are external and internal parties, where internal problems come from peers in the team, while the external parties are parents themselves. Trainers are assessed as rolemodels for students, so the coach is respected. The coach is able to be a friend to the players as well as being a team motivator.